The cracked mirror : an Indian debate on experience and theory - Guru, Gopal; Sarukkai, Sundar (New Delhi, India : Oxford University Press, 2017)
"An enduring challenge confronts the practice of social science in India and other non-western countries. For long, the experiences of these societies have been largely described by theoretical vocabulary and methods drawn from mainstream western intellectual traditions. This has led to two kinds of asymmetries in knowledge production in the social sciences. One is the overwhelming dependence on these western theories in order to make sense of non-western experiences along with the concomitant rejection of indigenous intellectual traditions. The other is the reluctance of the western academia to draw on both non-western writers as well as their intellectual traditions. The politics of these processes is that the experiences of the non-west are dominantly being defined by the theoretical constructs of the west. Using the format of a dialogue between two authors, this book confronts these issues by first beginning with an analysis of the nature of experience followed by an argument for an ethics of theorizing. These issues about the politics of experience and ethics of theory are discussed within the context of theorizing dalit experience and conceptualizing the problematic category of untouchability, by drawing upon both Indian and Western intellectual traditons"--Publisher's description.
Egalitarianism and the Social Science in India / Gopal Guru -- Experience and Theory: From Habermas to Gopal Guru / Sundar Sarukkai -- Understanding Experience / Sundar Sarukkai -- Experience, Space, and Justice / Gopal Guru -- Experience and the Ethics of Theory / Gopal Guru -- Ethics of Theorizing / Sundar Sarukkai -- Phenomenology of Untouchability / Sundar Sarukkai -- Archaeology of Untouchability / Gopal Guru.
"First edition published in 2012"--Title page verso.
Includes bibliographical references (pages 229-239) and index.
Imported from: zcat.oclc.org:210/OLUCWorldCat (Do not remove)
Keywords: Equality -- India; Social ethics -- India; Dalits -- India -- Social conditions